2008
DOI: 10.5194/angeo-26-2345-2008
|View full text |Cite
|
Sign up to set email alerts
|

Imaging observations of nighttime mid-latitude F-region field-aligned irregularities by an MU radar ultra-multi-channel system

Abstract: Abstract. Mid-latitude F-region field-aligned irregularities (FAIs) were studied by using the middle-and-upper atmosphere (MU) radar ultra-multi-channel system with the radar imaging technique. On 12 June 2006, F-region FAI echoes with a period of about one hour were observed intermittently. These echoes were found to be embedded in mediumscale traveling ionospheric disturbances (MSTIDs) observed as variations of total electron content (TEC). The echoes drifting away from (toward) the radar were observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…This interpretation is consistent with the results of previous studies conducted at Japanese sites [e.g., Saito et al , 2008; Otsuka et al , 2009]. In the previous studies, 2‐D structures of the F region 3‐m‐scale FAIs detected by the MU radar were compared with nighttime MSTIDs in the airglow images [ Otsuka et al , 2009] and the TEC map [ Saito et al , 2008]; the observations demonstrated that the measured northwestward (southeastward) FAI Doppler velocities coincided with the airglow/TEC depletions (enhancements). However, the 3‐m‐scale FAIs were observed as intermittent echo clusters that tended to occur at the airglow/TEC depletions, and hence, the observed Doppler velocities were mostly northwestward.…”
Section: Discussionsupporting
confidence: 94%
“…This interpretation is consistent with the results of previous studies conducted at Japanese sites [e.g., Saito et al , 2008; Otsuka et al , 2009]. In the previous studies, 2‐D structures of the F region 3‐m‐scale FAIs detected by the MU radar were compared with nighttime MSTIDs in the airglow images [ Otsuka et al , 2009] and the TEC map [ Saito et al , 2008]; the observations demonstrated that the measured northwestward (southeastward) FAI Doppler velocities coincided with the airglow/TEC depletions (enhancements). However, the 3‐m‐scale FAIs were observed as intermittent echo clusters that tended to occur at the airglow/TEC depletions, and hence, the observed Doppler velocities were mostly northwestward.…”
Section: Discussionsupporting
confidence: 94%
“…6 shows the RTI plots of (a-c) SNR and (moving away from the radar or upward velocities). The striation of the F-region echoes and the variation of the observed Doppler velocities, depending on the height rate of the striation, were similar to those observed by the MU radar in Japan , Saito et al 2008). (or Doppler velocity) was also identified from persistent echoes observed during other days.…”
Section: F-region Faissupporting
confidence: 79%
“…Several studies have investigated F-region irregularities in middle latitudes using radars in Japan (Fukao et al 1988, Otsuka et al 2009, Saito et al 1998, 2002, 2008 and Puerto Rico (Swartz et al 2000). Because the investigation of the F-region FAIs has been done as an event or on a campaign basis, the characteristics and distribution of the F-region FAIs have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…The drift velocity of the F ‐region plasma does not have a southwestward component because the polarization electric field is normal to the NW‐SE structure in cases RS1 and RS2. In fact, it has been found that small‐scale irregularities in the F region associated with the NW‐SE structure drift along the wavefront [ Saito et al , 2008]. It is the southward movement of polarization electric field distribution caused by the E ‐region southward wind that produces the phase propagation of the F ‐region NW‐SE structure because the F region is quickly modulated by the electric field mapped from the E region in the early stage of instability.…”
Section: Discussionmentioning
confidence: 99%